Method for preparing lithium manganese iron phosphate composite positive electrode material by utilizing multi-stage negative pressure evaporation
Through multi-stage negative pressure evaporation and two-stage sintering, the uneven particle size and waste liquid problems of lithium manganese iron phosphate composite positive electrode material in the prior art were solved, and materials with high stability and good conductivity were prepared, realizing that Green and environmentally friendly production process.
Patent Information
- Application Number
- CN202411330523.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-07
AI Technical Summary
In the preparation of lithium manganese iron phosphate composite positive electrode materials, the particle size distribution is not uniform, the dispersion is poor, the liquid phase reaction time is long, and the large amount of waste liquid is generated.
The lithium manganese iron phosphate composite positive electrode material was prepared by multi-stage negative pressure evaporation method, and the first and second-stage negative pressure evaporation and concentration were carried out through a rotary evaporator, and the air pressure and temperature were controlled to obtain uniform crystal crystals, and two were performed under a flowing inert atmosphere. Segment sintering.
Lithium manganese iron phosphate material with small particle size and good uniformity has been prepared, fast reaction, no waste waste slag production, and the stability and conductivity of the material have been significantly improved, which meets the requirements of sustainable development.
Smart Images

Figure BDA0005056738790000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a method for preparing lithium manganese iron phosphate composite positive electrode materials by using multi-stage negative pressure evaporation. Background Art
[0002] Olivine-type LiMPO4 (M=Fe, Mn) is considered to be a promising cathode material for lithium-ion batteries due to its high theoretical specific capacity, good thermal stability, cycle life, environmental friendliness and low cost. Among them, the biggest advantage of LiFePO4 cathode material is its high stability and no structural collapse, but its energy density and electronic conductivity are poor. The voltage platform of LiMnPO4 is about 4.1V, which is higher than the voltage platform of LiFePO4 (3.5V), which means that olivine-type LiMnPO4 can have a higher energy density, but its conductivity and stability are poor, and there is a problem of manganese dissolution. In order to combine the advantages of LiFePO4 and LiMnPO4, by adding Fe 2+ The larger Mn 2+ The obtained LiMn x Fe 1-x PO4 / C shows a higher voltage platform and energy density and has a more stable structure.
[0003] Existing synthetic LiMn x Fe 1-x There are many methods for synthesizing PO4 materials, mainly high-temperature solid-phase reaction method, liquid-phase coprecipitation method, hydrothermal method, sol-gel method, redox method, solid-phase microwave method and mechanical ball milling method, among which hydrothermal method is a commonly used synthesis method, which uses the aqueous solution environment under high temperature and high pressure to promote the dissolution and recrystallization of raw materials, thereby synthesizing LiMn with specific structure and performance. x Fe 1-x PO4 material, the final product has the advantages of good homogeneity, high crystallinity and controllable morphology, but the disadvantages of this method such as high equipment cost, complex operation and limited output also limit its commercial application to a certain extent. High temperature solid phase reaction method is another commonly used synthesis method. It is widely used in industrial production because of its relatively simple operation and easy control of reaction conditions, but it still has problems such as high energy consumption, long reaction time, difficulty in mixing uniformly, uneven particle size, and poor material rate performance. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method for preparing lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation, aiming to solve at least one technical problem in the background technology.
[0005] The present invention is achieved in that:
[0006] A method for preparing a lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation, the method comprising the following steps:
[0007] Put manganese acetate, ferrous sulfate and antioxidant in the same reaction kettle, add sufficient deionized water to completely dissolve them to form a manganese iron salt mixed solution; control the manganese iron salt mixed solution to maintain a constant temperature of 5°C to 40°C;
[0008] Mixed crystals of manganese acetate and ferrous sulfate are obtained by multi-stage negative pressure evaporation;
[0009] The mixed crystals are mixed with a lithium salt, a phosphorus-containing compound, and a carbon source, and ball-milled to obtain a precursor powder of lithium manganese iron phosphate;
[0010] The precursor powder is placed in a sintering furnace and sintered in two stages at a temperature range of 250°C to 850°C under a flowing inert atmosphere. The final powder product LiMn is obtained after cooling in the furnace. x Fe 1-x PO4 / C is the lithium manganese iron phosphate composite positive electrode material;
[0011] Among them; multi-stage negative pressure evaporation specifically includes:
[0012] The manganese iron salt mixed solution at a constant temperature is placed in a rotary evaporator, and the air pressure value inside the rotary evaporator is adjusted to reach the saturated vapor pressure according to the solution temperature and the following formula (I), and the air pressure is controlled to be 0.8KPa to 10KPa, and a first-level negative pressure evaporation concentration is performed under constant temperature and pressure;
[0013] When crystals are precipitated, the pressure is immediately and completely released to stop the evaporation of the manganese-iron salt mixed solution;
[0014] The manganese iron salt mixed solution is heated to 10° C. to 100° C. to completely dissolve the crystals, and then the pressure value inside the rotary evaporator is adjusted to reach the saturated vapor pressure according to the solution temperature and the following formula (I), and the pressure is controlled to be 1 KPa to 101 KPa, and two-stage negative pressure evaporation and concentration is performed at a constant temperature and pressure;
[0015] Continue evaporating until the liquid is completely evaporated to obtain uniformly precipitated mixed crystals of manganese acetate and ferrous sulfate, take out and put into an oven to remove remaining water to obtain dry mixed crystals;
[0016] The relationship between the air pressure value and the temperature of the manganese-iron salt mixed solution is expressed by the following formula (I):
[0017] ln(P)=9.3676-3826.36 / (228.04+T) (Ⅰ)
[0018] Wherein, P is the saturated vapor pressure, in MPa; T is the temperature of the manganese-iron salt mixed solution, in °C; the applicable range of formula (I) is T = 5 °C to 100 °C.
[0019] Furthermore, during the multi-stage negative pressure evaporation process, the error between the actual pressure value inside the rotary evaporator and the theoretical saturated vapor pressure value P calculated by formula (I) is no more than 3%.
[0020] Furthermore, the two-stage sintering specifically includes:
[0021] Heat to 250°C to 450°C at a heating rate of 5°C / min to 15°C / min, and sinter for 3h to 6h;
[0022] Heat to 600°C ~ 850°C at a heating rate of 5°C / min ~ 15°C / min, and sinter for 8h ~ 16h.
[0023] Furthermore, the molar ratio of the lithium salt, the phosphorus-containing compound, the manganese acetate and the ferrous sulfate is 1:1:1-1.2:x:1-x, 0.6≤x≤0.8.
[0024] Furthermore, the lithium salt is selected from lithium hydroxide, lithium nitrate, lithium acetate, lithium chloride, lithium acetate or lithium oxalate, preferably lithium hydroxide; the phosphorus-containing compound is selected from phosphoric acid, diammonium phosphate or triammonium phosphate, preferably diammonium phosphate or triammonium phosphate.
[0025] Furthermore, the carbon source is selected from glucose, sucrose, polyethylene glycol, citric acid or phenolic resin, preferably glucose or sucrose.
[0026] Furthermore, the mass of the carbon source is 1 / 12-1 / 6 of the total mass of the lithium salt, the phosphorus-containing compound, manganese acetate and ferrous sulfate.
[0027] Furthermore, the antioxidant is ascorbic acid.
[0028] Furthermore, the amount of the antioxidant is 5% to 10% of the mass of ferrous sulfate.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention utilizes negative pressure evaporation and concentration to simultaneously precipitate uniformly mixed crystals with small particle size. At the same time, the entire production process reacts quickly and no waste residue is generated. The prepared lithium manganese iron phosphate material has good stability and high electronic and ionic conductivity, which solves the problems of large particle size, uneven particle size distribution, poor dispersibility of lithium manganese iron phosphate prepared by the existing solid phase method and long reaction time of the liquid phase method and the generation of a large amount of waste liquid.
[0031] 2. The present invention uses multi-stage negative pressure concentration and water bath to evaporate and concentrate the simultaneously saturated solutions of iron salt and manganese salt at different fixed temperatures, so that manganese and iron elements are simultaneously and evenly precipitated into crystals in a certain proportion, avoiding crystal agglomeration caused by local oversaturation and improving the quality and uniformity of crystallization.
[0032] 3. The present invention avoids the generation of a large amount of waste liquid and waste residue, and consumes less energy. The entire preparation process is green, environmentally friendly and pollution-free, which fully meets the requirements of sustainable development. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] A method for preparing a lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation, the method comprising the following steps S11 to S14:
[0035] S11, preparing a mixed solution of manganese iron salt; the specific operation is as follows:
[0036] Weigh the raw materials: including lithium salt, phosphorus-containing compound, manganese acetate, ferrous sulfate, carbon source and antioxidant; the lithium salt is selected from lithium hydroxide, lithium nitrate, lithium acetate, lithium chloride, lithium acetate or lithium oxalate, preferably lithium hydroxide; the phosphorus-containing compound is selected from phosphoric acid, ammonium dihydrogen phosphate or triammonium phosphate, preferably ammonium dihydrogen phosphate or triammonium phosphate; the carbon source is selected from glucose, sucrose, polyethylene glycol, citric acid or phenolic resin, preferably glucose and sucrose; the antioxidant is ascorbic acid; wherein the molar ratio of lithium salt, phosphorus-containing compound, manganese acetate and ferrous sulfate is 1:1:1~1.2:x:1~x, 0.6≤x≤0.8; the mass of carbon source is 1 / 12~1 / 6 of the total mass of lithium salt, phosphorus-containing compound, manganese acetate and ferrous sulfate. The phosphorus-containing compound needs to be moderately excessive to increase the conversion rate of lithium salt; the amount of antioxidant is 5%~10% of the mass of ferrous sulfate.
[0037] Prepare a manganese iron salt mixed solution: place manganese acetate, ferrous sulfate and an antioxidant in the same reactor, add sufficient deionized water to completely dissolve them to form a manganese iron salt mixed solution; control the manganese iron salt mixed solution to maintain a constant temperature of 5°C to 40°C by a circulating cooler or water bath heating; the temperature can be 5°C, 20°C, 30°C, 40°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] S12, multi-stage negative pressure evaporation to obtain crystals; the specific operation is as follows:
[0039] (1) placing a manganese iron salt mixed solution at a constant temperature in a rotary evaporator, adjusting the air pressure inside the rotary evaporator to reach a saturated vapor pressure according to the solution temperature and the following formula (I), controlling the air pressure to be 0.8 KPa to 10 KPa, and performing first-stage negative pressure evaporation concentration at a constant temperature and pressure;
[0040] (2) when crystals precipitate, immediately and completely release the pressure to stop evaporation of the manganese-iron salt mixed solution;
[0041] (3) heating the manganese iron salt mixed solution to 10° C. to 100° C., so that the crystals are completely dissolved, adjusting the pressure value inside the rotary evaporator to reach the saturated vapor pressure according to the solution temperature and the following formula (I), controlling the pressure to be 1 KPa to 101 KPa, and performing secondary negative pressure evaporation and concentration at a constant temperature and pressure; the temperature may be 10° C., 80° C., 100° C., but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0042] (4) continuing evaporation until the liquid is completely evaporated to obtain uniformly precipitated mixed crystals of manganese acetate and ferrous sulfate, taking out and placing in an oven to remove remaining water to obtain dry mixed crystals;
[0043] Among them, in (1) and (3), the relationship between the pressure value inside the rotary evaporator and the temperature of the manganese iron salt mixed solution is expressed by the following formula (I):
[0044] ln(P)=9.3676-3826.36 / (228.04+T) (Ⅰ)
[0045] Wherein, P is the saturated vapor pressure, in MPa; T is the temperature of the manganese iron salt mixed solution, in °C; the applicable range of formula (I) is T = 5 °C to 100 °C;
[0046] In a specific implementation, the error between the actual gas pressure value inside the rotary evaporator and the theoretical saturated vapor pressure value P calculated by formula (I) is no more than 3%;
[0047] The solubility of manganese acetate and ferrous sulfate changes with the solution temperature, as shown in the following formulas (II) to (IV):
[0048] In the range of 10℃~100℃, the relationship between solution temperature and solubility of manganese acetate is:
[0049] S 乙酸锰 =1.976+5.011×10 -3 ×T+6.004×10 -4 ×T 2 Formula (II)
[0050] In the range of 10℃~60℃, the relationship between solution temperature and ferrous sulfate solubility is:
[0051] S 硫酸亚铁 =0.982+3.544×10 -2 ×T+1.500×10 -4 ×T 2 Formula (III)
[0052] In the range of 60℃~100℃, the relationship between solution temperature and ferrous sulfate solubility is:
[0053] S 硫酸亚铁 =7.23-6.651×10 -2 ×T+1.500×10 -4 ×T 2 Formula (IV)
[0054] Where, T is the temperature of the manganese-iron salt mixed solution, in °C, S 乙酸锰 and S 硫酸亚铁 They are the solubilities of manganese acetate and ferrous sulfate, respectively, in mol / L; and the above formula is the solubility-temperature relationship under normal pressure. However, within the above pressure range, the effect of pressure on solubility is small and can be ignored.
[0055] The present invention uses multi-stage negative pressure evaporation and concentration to prepare lithium manganese iron phosphate; manganese salt and iron salt have different solubility ratios at different temperatures, and the solution of iron salt and manganese salt saturated at the same time is evaporated and concentrated at different fixed temperatures by negative pressure and water bath, so that manganese and iron elements are simultaneously and evenly precipitated into crystals in a certain proportion. In addition, multi-stage evaporation can avoid crystal agglomeration caused by local oversaturation, and improve the quality and uniformity of crystallization.
[0056] S13, preparing a precursor; the specific operation is as follows:
[0057] The mixed crystals are mixed with lithium salt, phosphorus-containing compound and carbon source, and placed in a ball mill together with agate balls, and ball milled at a speed of 300 rpm to 400 rpm for about 5 hours to obtain precursor powder of lithium manganese iron phosphate;
[0058] S14, sintering to prepare positive electrode materials; the specific operation is as follows:
[0059] The precursor powder is placed in a sintering furnace under a flowing inert atmosphere, first heated to 250°C to 450°C at a heating rate of 5°C / min to 15°C / min, sintered for 3h to 6h, then heated to 600°C to 850°C at a heating rate of 5°C / min to 15°C / min, sintered for 8h to 16h; finally, the final powder product LiMn is obtained after cooling in the furnace. x Fe 1-xPO4 / C is the manganese iron lithium phosphate composite positive electrode material. The heating rate can be 5℃ / min, 10℃ / min, 15℃ / min; the first stage sintering temperature can be 250℃, 350℃, 450℃, and the first stage heat preservation sintering time can be 3h, 4.5h, 6h; the first stage sintering temperature can be 300℃, 750℃, 800℃, and the first stage heat preservation sintering time can be 8h, 12h, 16h, but not limited to the listed values, and other unlisted values within the numerical range are also applicable. The high-temperature sintering is carried out in a flowing inert atmosphere (the inert atmosphere is one or more of argon, nitrogen or helium) throughout the process to prevent product oxidation.
[0060] Example 1
[0061] A method for preparing a lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation, the method comprising the following steps:
[0062] S11, weigh lithium hydroxide (110.7 g, 1.0 eq, purity ≥ 99.9%), ammonium dihydrogen phosphate (584.6 g, 1.1 eq, analytical grade), high-purity manganese acetate (563.2 g, 0.7 eq, purity ≥ 99.9%), ferrous sulfate (207.6 g, 0.3 eq, purity ≥ 99.9%) and 146.6 g glucose; put the weighed manganese acetate, ferrous sulfate and 12 g ascorbic acid into the same reactor, add 2 L of deionized water to completely dissolve the substances; and maintain the solution temperature at 30° C. by heating in a water bath;
[0063] S12, use a high-precision rotary vane vacuum pump to perform multi-stage evaporation, first place a 30°C manganese iron salt mixed solution in a rotary evaporator, control its air pressure at about 4.25KPa, so that the solution begins to evaporate and concentrate under a relatively high vacuum condition; during the period, when crystals appear in the rotary evaporator, the pressure is immediately released, and the solution no longer boils; then the solution temperature is raised to 83°C by heating in a water bath, and after the precipitated crystals are completely dissolved again, the rotary vane vacuum pump is turned on to control the air pressure at 53.60KPa, so that the solution boils again, and the temperature and air pressure remain unchanged and continue to evaporate until the liquid is completely evaporated to obtain uniformly precipitated manganese acetate and ferrous sulfate mixed crystals, and the remaining water is dried in an oven after taking out to obtain dry mixed crystals;
[0064] S13, mixing the mixed crystals obtained in S12 with lithium hydroxide, ammonium dihydrogen phosphate and glucose, placing the mixture in a ball mill together with an agate ball, and ball milling at a speed of 300 rpm for about 5 hours to obtain a precursor powder of lithium manganese iron phosphate;
[0065] S14, put the precursor powder obtained in S13 into a sintering furnace for sintering. The sintering temperature is carried out in two stages, and the heating rate is 10℃ / min for both times. The working temperature of the first stage is 450℃, and the temperature is kept for 6h; the working temperature of the second stage is 800℃, and the temperature is kept for 10h. The high-temperature sintering is carried out in flowing argon gas to prevent oxidation of the product. After cooling in the furnace, the final powder product LiMn is obtained. 0.7 Fe 0.3 PO4 / C.
[0066] Example 2
[0067] A method for preparing a lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation, the method comprising the following steps:
[0068] S11, weigh lithium hydroxide (41.4g, 1.0eq, purity ≥99.9%), triammonium phosphate (309.5g, 1.2eq, analytical grade), high-purity manganese acetate (180.8g, 0.6eq, purity ≥99.9%), ferrous sulfate (104.1g, 0.4eq, purity ≥99.9%) and 53.0g sucrose; put the weighed manganese acetate, ferrous sulfate and 10g ascorbic acid in the same reactor, add 1L deionized water to completely dissolve the substances; and cool the solution by a circulating cooler to maintain the solution temperature at 5°C;
[0069] S12, use a high-precision rotary vane vacuum pump to perform multi-stage evaporation, first place a 5°C manganese iron salt mixed solution in a rotary evaporator, control its air pressure at about 0.87KPa, so that the solution begins to evaporate and concentrate under a relatively high vacuum condition; during the period, when crystals appear in the rotary evaporator, the pressure is immediately released, and the solution no longer boils; then the solution temperature is raised to 10°C by heating in a water bath, and after the precipitated crystals are completely dissolved again, the rotary vane vacuum pump is turned on to control the air pressure at 1.23KPa, so that the solution boils again, and the temperature and air pressure remain unchanged and continue to evaporate until the liquid is completely evaporated to obtain uniformly precipitated manganese acetate and ferrous sulfate mixed crystals, and the remaining water is dried in an oven after taking out to obtain dry mixed crystals;
[0070] S13, mixing the mixed crystals obtained in S12 with lithium hydroxide, triammonium phosphate and sucrose, placing the mixture in a ball mill together with an agate ball, and ball milling at a speed of 400 rpm for about 5 hours to obtain a precursor powder of lithium manganese iron phosphate;
[0071] S14, put the precursor powder obtained in S13 into a sintering furnace for sintering. The sintering temperature is carried out in two stages, and the heating rate is 5℃ / min for both times. The working temperature of the first stage is 250℃, and the temperature is kept for 3h; the working temperature of the second stage is 600℃, and the temperature is kept for 8h. The high-temperature sintering is carried out in flowing argon gas to prevent oxidation of the product. After cooling in the furnace, the final powder product LiMn is obtained. 0.6 Fe 0.4 PO4 / C.
[0072] Example 3
[0073] A method for preparing a lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation, the method comprising the following steps:
[0074] S11, weigh lithium hydroxide (126.8g, 1.0eq, purity ≥99.9%), ammonium dihydrogen phosphate (730.1g, 1.2eq, analytical grade), high-purity manganese acetate (736.2g, 0.8eq, purity ≥99.9%), ferrous sulfate (158.1g, 0.2eq, purity ≥99.9%) and 145.9g glucose; put the weighed manganese acetate, ferrous sulfate and 15g ascorbic acid into the same reactor, add 1L of deionized water to completely dissolve the substances; and cool the solution by a circulating cooler to maintain the solution temperature at 20°C;
[0075] S12, use a high-precision rotary vane vacuum pump to perform multi-stage evaporation, first place a 20°C manganese iron salt mixed solution in a rotary evaporator, and control its air pressure at about 2.34KPa, so that the solution begins to evaporate and concentrate under a relatively high vacuum condition; during the period, when crystals appear in the rotary evaporator, the pressure is immediately released, and the solution no longer boils; then the solution temperature is raised to 100°C by heating in a water bath, and after the precipitated crystals are completely dissolved again, the rotary vane vacuum pump is turned on and the air pressure is controlled at 100KPa, so that the solution boils again, and the temperature and air pressure remain unchanged and continue to evaporate until the liquid is completely evaporated to obtain uniformly precipitated mixed crystals of manganese acetate and ferrous sulfate, and the remaining water is dried in an oven after taking out to obtain dry mixed crystals;
[0076] S13, mixing the mixed crystals obtained in S12 with lithium hydroxide, triammonium phosphate and sucrose, placing the mixture in a ball mill together with an agate ball, and ball milling at a speed of 350 rpm for about 5 hours to obtain a precursor powder of lithium manganese iron phosphate;
[0077] S14, put the precursor powder obtained in S13 into a sintering furnace for sintering. The sintering temperature is carried out in two stages, and the heating rate is 15℃ / min for both times. The working temperature of the first stage is 300℃, and the temperature is kept for 6h; the working temperature of the second stage is 850℃, and the temperature is kept for 10h. The high-temperature sintering is carried out in flowing argon gas to prevent oxidation of the product. After cooling in the furnace, the final powder product LiMn is obtained. 0.8 Fe 0.2 PO4 / C.
[0078] Comparative Example 1
[0079] This comparative example is a method for preparing a lithium manganese iron phosphate composite positive electrode material by negative pressure evaporation. The difference between this comparative example and Example 1 is only in step S12. Step S12 of this comparative example adopts single-stage negative pressure evaporation concentration, and the other steps and reaction conditions are the same as those of Example 1.
[0080] Step S12 of this comparative example is specifically as follows: a single evaporation is performed using a high-precision rotary vane vacuum pump. First, the air pressure in the rotary evaporator is accurately controlled at 53.60 KPa, and the solution temperature is raised to 83° C. by heating in a water bath to make the solution boil. The temperature and air pressure remain unchanged and the evaporation is continued until the liquid is completely evaporated to obtain uniformly precipitated mixed crystals of manganese acetate and ferrous sulfate. After taking out, the mixed crystals are placed in an oven to dry the remaining water to obtain dry mixed crystals.
[0081] Comparative Example 2
[0082] This comparative example is a method for preparing an existing lithium iron manganese phosphate composite positive electrode material, specifically, a method for preparing a lithium iron manganese phosphate electrode material according to Example 4 in CN108539161A, and the specific steps are as follows:
[0083] 0.06mol lithium chloride is dissolved in 15ml ethylene glycol solvent to obtain A solution, 0.02mol phosphoric acid is dissolved in 20ml ethylene glycol solvent simultaneously, 0.0025mol sodium lauryl sulfate is added subsequently and the sodium lauryl sulfate (B mixed solution) that uniform dispersion obtains phosphoric acid is evenly dispersed. Phosphoric acid solution is dropwise added in lithium chloride solution, and phosphoric acid solution dropping rate is less than 1ml / min, and continuous stirring 20min obtains suspension C. 0.012mol manganese oxalate and 0.008mol ferrous oxalate are dissolved in 20ml ethylene glycol solvent to obtain D mixed solution, and the ascorbic acid of 0.02mol / L is added to prevent the oxidation of metal ions. Prepared mixed solution D is slowly poured into above-mentioned suspension C subsequently, and dropping rate is less than 2ml / min, and after strong stirring 30min, pours into 100ml reactor. Keep warm at 160°C for 15 hours, cool to room temperature, take out the generated liquid, use a centrifuge to centrifuge, filter out the supernatant, add deionized water and anhydrous ethanol to wash 3 to 5 times until the solution is transparent, take out the precipitate and dry it. After drying, grind to obtain lithium manganese phosphate powder. Dissolve 1.0g of lithium manganese phosphate powder and 0.05g of starch in 15mol of anhydrous ethanol, stir the slurry magnetically for 3h and dry it naturally at room temperature, heat the powder from room temperature to 550°C, calcine for 12h in an inert gas atmosphere, and then grind to obtain a carbon-coated lithium manganese phosphate material, heat the powder from room temperature to 800°C at a heating rate of 5°C / min, keep warm for 5h in an argon-hydrogen (5% H2-95% Ar) atmosphere, and cool to room temperature to obtain LiMn 0.6 Fe 0.4 PO4 / C powder, particle size D50 is 1.9μm.
[0084] Comparative Example 3
[0085] This comparative example is a method for preparing a lithium manganese iron phosphate composite positive electrode material by negative pressure evaporation. The difference between this comparative example and Example 1 is that the pressure value used in each level of negative pressure evaporation concentration in step S12, that is, the error between the pressure value and the saturated vapor pressure value calculated by formula (I) exceeds 3%; the other steps and reaction conditions are the same as those in Example 1;
[0086] In this comparative example, the pressure value of the first negative pressure evaporation concentration is set to 3.5 KPa; the pressure value of the second negative pressure evaporation concentration is set to 45 KPa, both of which are more than 3% lower than the saturated vapor pressure value calculated by formula (I).
[0087] In order to conduct the charge and discharge specific capacity test, the prepared lithium manganese iron phosphate composite positive electrode material needs to be made into an electrode plate, and then assembled into a battery; specifically: the lithium manganese iron phosphate composite positive electrode material, the binder PVDF and the conductive agent acetylene black are mixed in a mass ratio of 8:1:1 in a high-energy ball mill to obtain a uniformly mixed black slurry, and then the black slurry is evenly coated on the current collector aluminum foil by a coating machine, and finally dried at 100°C in a vacuum drying oven for 12 hours to obtain a plate; after flattening, it is cut into a circular plate with a diameter of 15 mm; the circular plate is used as the positive electrode, the metal lithium sheet is used as the negative electrode, Celgard2400 is used as the diaphragm, and 1M LiPF6 EC:DMC (1:1 Vol%) is used as the electrolyte, and a button battery is assembled according to the positive electrode shell→positive electrode plate→diaphragm→lithium sheet→gasket, shrapnel→negative electrode shell, and electrochemical tests such as charge and discharge specific capacity are carried out on a Land electrochemical instrument.
[0088] The button cells made of lithium manganese iron phosphate composite positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for charge and discharge specific capacity at discharge rates of 0.1C and 2C. The initial discharge capacity and capacity retention rate results obtained after 100 cycles are shown in Table 1.
[0089] Table 1
[0090]
[0091] As can be seen from the data in Table 1, from the particle size distribution of Examples 1 to 3, it can be seen that the particle size distribution of the lithium manganese iron phosphate composite positive electrode material product prepared by the present invention is more uniform. Compared with the single negative pressure evaporation concentration in Comparative Example 1, the present invention prepares LiMn with excellent dispersibility, electronic conductivity and stability. x Fe 1-x The discharge capacity and capacity retention rate of the final product PO4 / C are higher than those of Comparative Example 1 and the prior art (Comparative Example 2).
[0092] In Comparative Example 3, two-stage negative pressure evaporation and concentration were used, but the gas pressure setting did not comply with the requirements of formula (I). From the data in Table 1, it can be seen that the electrochemical performance of the lithium manganese iron phosphate composite positive electrode material obtained in Comparative Example 3 is lower than that in Example 1. The reason is that the gas pressure in Comparative Example 3 is too low, and the boiling point of the liquid is much lower than the theoretical temperature, that is, the water bath heating temperature is too high, and the heat transfer rate to the solution is too fast, resulting in uneven temperature distribution in the solution, local large-particle crystal precipitation, and reduced uniformity of grain size, which affects the final performance.
[0093] In addition, when the air pressure is too high, the boiling point will be higher than the actual temperature, the solution will not evaporate, and negative pressure evaporation concentration cannot be carried out. Therefore, if two-stage negative pressure evaporation concentration is used, the air pressure value cannot exceed the theoretical value too much.
[0094] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation, characterized in that: The method comprises the following steps: Put manganese acetate, ferrous sulfate and antioxidant in the same reaction kettle, add sufficient deionized water to completely dissolve them to form a manganese iron salt mixed solution; control the manganese iron salt mixed solution to maintain a constant temperature of 5°C to 40°C; Mixed crystals of manganese acetate and ferrous sulfate are obtained by multi-stage negative pressure evaporation; The mixed crystals are mixed with a lithium salt, a phosphorus-containing compound, and a carbon source, and ball-milled to obtain a precursor powder of lithium manganese iron phosphate; The precursor powder is placed in a sintering furnace and sintered in two stages at a temperature range of 250°C to 850°C under a flowing inert atmosphere. The final powder product LiMn is obtained after cooling in the furnace. x Fe 1-x PO4 / C is the lithium manganese iron phosphate composite positive electrode material; in; Multi-stage negative pressure evaporation specifically includes: The manganese iron salt mixed solution at a constant temperature is placed in a rotary evaporator, and the air pressure value inside the rotary evaporator is adjusted to reach the saturated vapor pressure according to the solution temperature and the following formula (I), and the air pressure is controlled to be 0.8KPa to 10KPa, and a first-level negative pressure evaporation concentration is performed under constant temperature and pressure; When crystals are precipitated, the pressure is immediately and completely released to stop the evaporation of the manganese-iron salt mixed solution; The manganese iron salt mixed solution is heated to 10° C. to 100° C. to completely dissolve the crystals, and then the pressure value inside the rotary evaporator is adjusted to reach the saturated vapor pressure according to the solution temperature and the following formula (I), and the pressure is controlled to be 1 KPa to 101 KPa, and two-stage negative pressure evaporation and concentration is performed at a constant temperature and pressure; Continue evaporating until the liquid is completely evaporated to obtain uniformly precipitated mixed crystals of manganese acetate and ferrous sulfate, take out and put into an oven to remove remaining water to obtain dry mixed crystals; The relationship between the air pressure value and the temperature of the manganese-iron salt mixed solution is expressed by the following formula (I): ln(P)=9.3676-3826.36 / (228.04+T) (Ⅰ) Wherein, P is the saturated vapor pressure, in MPa; T is the temperature of the manganese-iron salt mixed solution, in °C; the applicable range of formula (I) is T = 5 °C to 100 °C.
2. The method for preparing lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation according to claim 1, characterized in that: In the multi-stage negative pressure evaporation process, the error between the actual pressure value inside the rotary evaporator and the theoretical saturated vapor pressure value P calculated by formula (I) is no more than 3%.
3. The method for preparing lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation according to claim 1, characterized in that: The two-stage sintering specifically includes: Heat to 250°C to 450°C at a heating rate of 5°C / min to 15°C / min, and sinter for 3h to 6h; Heat to 600°C ~ 850°C at a heating rate of 5°C / min ~ 15°C / min, and sinter for 8h ~ 16h.
4. The method for preparing lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation according to claim 1, characterized in that: The molar ratio of lithium salt, phosphorus-containing compound, manganese acetate and ferrous sulfate is 1:1:1-1.2:x:1-x, 0.6≤x≤0.
8.
5. The method for preparing lithium iron manganese phosphate composite positive electrode material by multi-stage negative pressure evaporation according to claim 4, characterized in that: The lithium salt is selected from lithium hydroxide, lithium nitrate, lithium acetate, lithium chloride, lithium acetate or lithium oxalate, and the phosphorus-containing compound is selected from phosphoric acid, diammonium phosphate or triammonium phosphate.
6. The method for preparing lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation according to claim 1, characterized in that: The carbon source is selected from glucose, sucrose, polyethylene glycol, citric acid or phenolic resin.
7. The method for preparing lithium iron manganese phosphate composite positive electrode material by multi-stage negative pressure evaporation according to claim 6, characterized in that: The mass of the carbon source is 1 / 12-1 / 6 of the total mass of the lithium salt, the phosphorus-containing compound, manganese acetate and ferrous sulfate.
8. The method for preparing lithium manganese iron phosphate composite positive electrode material by multi-stage negative pressure evaporation according to claim 1, characterized in that: The antioxidant is ascorbic acid.
9. The method for preparing lithium iron manganese phosphate composite positive electrode material by multi-stage negative pressure evaporation according to claim 8, characterized in that: The dosage of the antioxidant is 5% to 10% of the mass of ferrous sulfate.
Citation Information
Patent Citations
Preparation method of olive-shaped lithium manganese phosphate with prismatic protrusions
CN108539161A
Cited By
Solid powder salt pH value control method and device for sedimentation test
CN120595882A